DETERMINATION OF TETRACYCLINE GROUP ANTIBIOTICS RESIDUES IN THE TIGRIS RIVER AND AGRICULTURAL LANDS FED BY TIGRIS RIVER AND REDUCTION OF UNCONSCIOUS USE OF ANTIBIOTICS - Ozcan, Filiz; Celik, Aytekin; Arserim, Neval Berrin (Publ House Bulgarian Acad Sci, 2024)
The recent increase in environmental pollutants is contaminating important natural resources and causing irreversible damage. Due to the limitations of traditional treatment techniques, studies on the problem of micro pollutant contamination of water resources have increased significantly. Antibiotics used in medicine and veterinary medicine cause significant pollution of water resources as residues of these contaminants remain unchanged in the aqueous environment. This has recently been recognised as a global environmental health threat. The ecosystem is vulnerable to residues of these contaminants from agriculture and aquaculture. In this study, the presence of tetracycline group antibiotics, the most commonly used in veterinary medicine, was determined in the Tigris river. This is the first study to date in which antibiotics from the tetracycline group have been identified in the Tigris river. Water samples were taken from 16 different points (80 samples) along the river. Sampling points were grouped as abattoirs, livestock markets, farmland, cafes and bridges near settlements. The samples were analysed for the presence of tetracycline (TC), oxytetracycline (OTC) and chlortetracycline (CTC). With a concentration range of 0.037 to 1.756 ng/L, oxytetracycline was found in 14 of the 16 sites. A concentration of 0.004-0.014 ng/L of tetracycline was found in five samples. Chlortetracycline was found in six samples, with concentrations ranging from 0.015 to 0.097 ng/L. According to the study, the tetracycline family of antibiotics was found in the water samples, and oxytetracycline was present in the highest concentrations in most of them.
Keywords: Tigris river; tetracycline; oxytetracycline; chlortetracycline; antibiotic